Sun safety in construction: a UK intervention study - Houdmont, Jonathan; Madgwick, P.; Randall, R. (Oxford Journals, 2016)
Background: Interventions to promote sun safety in the UK construction sector are warranted given the high incidence of skin cancer attributable to sun exposure relative to other occupational groups. Aims: To evaluate change in sun safety knowledge and practices among construction workers in response to an educational intervention. Methods: A baseline questionnaire was administered, followed by a bespoke sector-specific DVD-based intervention. At 12-month follow-up participants completed a further questionnaire. Results: Analyses were conducted on a sample of 120 workers (intervention group, n = 70; comparison group, n = 50). At follow-up the proportion of intervention group participants that reported correct sun safety knowledge was not significantly greater than at baseline. However, the intervention group demonstrated significant positive change on nine out of ten behavioural measures, the greatest change being use of a shade/cover when working in the sun followed by regularly checking skin for moles or unusual changes. Conclusions: Exposure to this intervention was linked to some specific positive changes in construction workers’ self-reported sun safety practices. These findings highlight the potential for educational interventions to contribute to tackling skin cancer in the UK construction sector. The findings support the development of bespoke educational interventions for other high-risk outdoor worker groups.